Implementasi Pendidikan Karakter dalam Proses Pembelajaran Akidah Akhlak di SMP Negeri 1 Karawang Timur - Muhammad Agiel Dwi Putra; Ajat Rukajat; Khalid Ramdhani (ISLAMIKA, 2022)
This research is motivated by the decline in the character of students who are experiencing moral decadence, for example, such as the number of promiscuity, using illegal drugs, students who often skip school, bullying, and so on. Therefore, to deal with this problem, schools, especially in learning Akidah Akhlak, have a big role in instilling Islamic religious values in students. This study used qualitative research methods. The location of this research is carried out in SMP Negeri 1 Karawang Timur. Data collection techniques used in this study are using observation, interviews, and documentation. The results of this study indicate that: (1) Akhlak teacher learning planning in an effort to build student character is by preparing a Akidah Akhlak learning plan, (2) In an effort to build student character through Akidah Akhlak learning is carried out in accordance with the planned rules and regulations. determined in the Akidah Akhlak learning process, (3) Evaluation of Akidah Akhlak learning is usually in the form of exams, daily tests, UTS and UAS. In the delivery of learning Akidah Akhlak in the formation of student character is instilled by subject teachers and produces satisfactory results.